Importing inequality: Immigration and the top 1 percent - Arun Advani; Felix Koenig; Lorenzo Pessina; Andy Summers (Institute for Fiscal Studies (IFS), 2020)
In this paper we study the contribution of migrants to the rise in UK top incomes. Using administrative data on the universe of UK taxpayers we show migrants are over-represented at the top of the income distribution, with migrants twice as prevalent in the top 0.1% as anywhere in the bottom 97%. These high incomes are predominantly from labour, rather than capital, and migrants are concentrated in only a handful of industries, predominately finance. Almost all (85%) of the growth in the UK top 1% income share over the past 20 years can be attributed to migration.
Keywords: H2; J3; J6; 330; Einkommensverteilung; Vermögensverteilung; Migranten; Großbritannien